Factors Influencing the Utilization of Health Services for JKN-KIS Participants (Study: Grilled Pematang III.B Health Center, Mesuji Makmur District, Ogan Komering Ilir Regency) - Muhammad Amin Azhari; Andy Alfatih; Sena Putra Prabujaya (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to determine whether there is an influence of the level of knowledge of JKN-KIS participants, the attitude of health workers and the accessibility of health facilities simultaneously on the utilization of health services for JKN-KIS participants at Community Health Centers and their networks.The method used in this study is a quantitative method. Minimum of 99 samples from JKN-KIS participants in the work area of ​​Pematang Panggang III.b Health Center, Mesuji Makmur District, Ogan Komering Ilir Regency. In this study, there were two hypothesis tests, namely the Partial Significance Test (T-Test) and the Simultaneous Test (F-Test). The data analysis technique used descriptive statistical analysis techniques; multiple linear regression analysis. The results showed that the level of knowledge of JKN-KIS participants did not have a significant effect on the utilization of health services at the Pematang Panggang III.b Health Center, Mesuji Makmur District and its network. The accessibility of health facilities had a positive and significant effect on the utilization of health services for JKN-KIS participants at the Pematang Panggang III.b Health Center, Mesuji Makmur District. The level of knowledge of JKN-KIS participants, the attitude of health workers and the accessibility of health facilities simultaneously had a positive and significant effect on the utilization of health services for JKN-KIS participants at the Pematang Panggang III.b Health Center, Mesuji Makmur District, Prosperous Mesuji.